2019
DOI: 10.3390/cancers11091298
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Renal Cell Carcinomas Rewire Glutathione Metabolism and Are Deficient in Both Anabolic Glucose Synthesis and Oxidative Phosphorylation

Abstract: Papillary renal cell carcinoma (pRCC) is a malignant kidney cancer with a prevalence of 7–20% of all renal tumors. Proteome and metabolome profiles of 19 pRCC and patient-matched healthy kidney controls were used to elucidate the regulation of metabolic pathways and the underlying molecular mechanisms. Glutathione (GSH), a main reactive oxygen species (ROS) scavenger, was highly increased and can be regarded as a new hallmark in this malignancy. Isotope tracing of pRCC derived cell lines revealed an increased … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…1E), consistent with a previous study performed in chRCC (31). Interestingly, a similar pattern was reported in other RCC subtypes, including ccRCC (13), pRCC (32), and renal oncocytoma (17,33). Thus, the increase of glutathione has been proposed as a hallmark of kidney cancer and targeting glutathione metabolism can be exploited as a specific treatment strategy (34).…”
Section: Proteome and Metabolome Profiling Of Chrccsupporting
confidence: 89%
See 1 more Smart Citation
“…1E), consistent with a previous study performed in chRCC (31). Interestingly, a similar pattern was reported in other RCC subtypes, including ccRCC (13), pRCC (32), and renal oncocytoma (17,33). Thus, the increase of glutathione has been proposed as a hallmark of kidney cancer and targeting glutathione metabolism can be exploited as a specific treatment strategy (34).…”
Section: Proteome and Metabolome Profiling Of Chrccsupporting
confidence: 89%
“…Kidney is the only organ, besides liver, that can deliver anabolic glucose for the organism, but a net flux can be generated only in one direction to avoid a futile cycle, which would violate thermodynamics. All kidney tumors seem to abandon this energy-consuming pathway since similar observations were also reported at the proteome level in renal oncocytomas (17), chRCC (49), and pRCC (32) and at the transcript level in pRCC (50) and ccRCC (30). A loss of differentiation, common in cancer, is indicated by the observed changes in the abundance of these gluconeogenic proteins.…”
Section: Discussionsupporting
confidence: 70%
“…Investigations have shown that increased expression of Talin-1 could lead to the progression of tumor cell adhesion and migration because of Talin-1 as a FA protein is able to mediate integrin interaction with ECM and can bind to a variety of adhesion molecules and induce cell cytoskeleton remodeling (23). B7-H3, also a member of the B7 family of immunoregulatory proteins which is overexpressed in many types of malignancies and is linked to poor prognosis, increased tumor grade, and metastasis (57).…”
Section: Discussionmentioning
confidence: 99%
“…RCC are mostly consist of three subtypes, renal clear cell carcinoma (KIRC), renal papillary cell carcinoma (KIRP), and renal chromophobe cell carcinoma (KICH) 2 . Renal clear cell carcinoma (KIRC) constitutes 70 percent of all RCC cases, while renal papillary cell carcinoma (KIRP) is the second common subtype of RCC and occupies 15 percent 3 . Clinically, KIRP is considered as more inert than KIRC.…”
Section: Introductionmentioning
confidence: 99%